POLITICAL COMMUNICATION AND ISLAMIC-BASED POLITICAL DIPLOMACY: THE ROLE OF SYEIKH ALI AKBAR MARBUN IN PLURAL SOCIETY OF NORTH SUMATRA, INDONESIA - Muhammad Safikqi Juanda Lubis; Mohd Syakir Bin Mohd Rosdi (OPINI: Journal of Communication and Social Science, 2026)
This article examines how Islamic-based political communication operates as a form of political diplomacy in a pluralistic society, focusing on the case of Syeikh Ali Akbar Marbun in North Sumatra, Indonesia. The study employs a qualitative case study design based on document analysis of twenty-three sources collected between January and June 2024, including religious sermons, institutional publications from Pesantren Al-Kautsar Al-Akbar, biographical narratives, and academic writings discussing the public role of the ulama. The findings show that Syeikh Ali Akbar Marbun acts as a non-state political communicator through ethical and symbolic communication practices such as elite visits (sowan), sermons addressing leadership ethics, and informal consultations with political actors. These communicative practices function as symbolic mechanisms that reinforce moral legitimacy, encourage ethical reflection among political elites, and facilitate dialogue across religious and ethnic boundaries. The novelty of this study lies in conceptualizing ulama as ethical political communicators who perform informal diplomatic functions through symbolic and relational communication practices in plural democratic societies.